WRITING PHD THESIS IN ENGLISH: IMPORTANCE, CHALLENGES, AND THESIS ORIGINALITY - Milovanovic, Petar; Stolic, Dragana; Pekmezovic, prof. dr Tatjana (Medical Research, 2023)
In line with the ORPHEUS guidelines, to encourage international recognition of PhD theses, Faculty of Medicine University of Belgrade (FMUB) promotes writing PhD theses in English. FMUB also requests and encourages PhD candidates to publish their results in international journals before thesis submission in order to increase their visibility in scientific community. In addition to specific topics in medicine, PhD education needs to cover the topics of general interest to researchers, in particular copyright and originality issues in scientific research. By adopting the concepts and terms of copyright, PhD candidates learn the importance of intellectual property and avoid plagiarism. As writing PhD thesis in English may increase the textual overlap between the thesis and the candidate’s own published papers (in English) originated from the thesis, there may be some dilemmas in practice whether such textual overlap should be considered self-plagiarism or not. In line with the regulations at the top universities in the field of medicine, FMUB has adopted the conclusion that textual overlap between the thesis and the thesis-based publications of the candidate does not represent self-plagiarism, provided that certain conditions are met. Namely, regardless of the language of the dissertation, the key aspects of academic integrity in writing PhD thesis should be honesty and transparency: transparently linking the thesis-based publications with the final thesis; honestly and appropriately referencing the statements or any other content taken from the candidate’s own previous work (unrelated to thesis) or other people’s work; and transparently acknowledging the contribution from coauthors and team members in the thesis. These recommendations will improve transparency of thesis writing, protect PhD candidates and their supervisors, enhance internationalization of PhD programs, and further promote academic honesty in medical research and publishing.